HUBUNGAN KADAR NEURON SPECIFIC ENOLASE SERUM TERHADAP LUARAN KLINIS NEUROLOGIS PASIEN STROKE ISKEMIK AKUT - Christina Roseville Lasma Aritonang; Retnaningsih Retnaningsih; Amin Husni (PERDOSNI, 2018)
CORRELATION OF SERUM NEURON SPECIFIC ENOLASE AND CLINICAL NEUROLOGICAL OUTCOME IN ACUTE ISCHEMIC STROKE PATIENTSABSTRACTIntroduction: Stroke is a neurological disease that cause disability. Ischemic stroke occurs in 85-87% of all cases. The biochemical markers of acute neuron injury can help in diagnosis and management of cerebrovascular injury. Neuron specific enolase (NSE) is dimeric isoenzymes of glycolytic enolase enzymes and found mainly in neurons as one of the markers in acute neuronal injury and can be estimated to assess short-term neurological outcome.Aims: To know the relationship of serum NSE level with stroke severity (? NIHHS) in acute ischemic stroke.Methods: This was an observational analytic study with a prospective cohort approach. Subjects were patients diagnosed with acute ischemic stroke who met the inclusion criteria. Numeric and categoric variables relationship test was performed using Mann-Whitney. Relationship between categoric variables with χ2 test, Fisher test and Kolmogorov- Smirnov 2 sample test. The results of bivariate analysis with p<0.25 were further analyzed by multivariate logistic regression test to determine the variables that influence the NIHSS score change.Results: There were 42 subjects with average age of 61.6±12.3 years with male sex more dominant. There was no significant relationship between serum NSE levels and ? NIHSS of acute ischemic stroke (p=0.446).Discussion: Neuron Specific Enolase levels were not related to changes in the NIHSS score of acute ischemic stroke, there was a significant relationship between BMI status and changes in NIHSS.Keywords: Acute ischemic stroke, ? NIHSS score, NSE serumABSTRAKPendahuluan: Stroke merupakan suatu penyakit neurologi dan penyebab disabilitas di seluruh dunia. Sroke Iskemik terjadi pada 85-87% dari seluruh kasus. Penanda biokimiawi dari cedera neuron akut dapat membantu diagnosis dan manajemen stroke serebrovaskular. Neuron specific enolase (NSE) merupakan isoenzim dimerik dari enzim enolase glikolitik dan ditemukan terutama di neuron adalah penanda yang dilepaskan dalam darah pada cedera neuron akut dan dapat diperkirakan dalam serum pasien untuk menilai derajat defisit neurologis jangka pendek.Tujuan: Mengetahui hubungan kadar penanda NSE serum dengan derajat keparahan stroke (? NIHSS) pada stroke iskemik akut.Metode: Penelitian ini merupakan penelitian observasional analitik dengan pendekatan kohort prospektif. Subjek adalah pasien yang didiagnosis stroke iskemik akut yang memenuhi kriteria inklusi. Uji hubungan variabel berskala numerik dan kategorial menggunakan uji Mann-Whitney. Hubungan antara variabel kategorial didapatkan dengan uji χ2, uji Fisher dan uji Kolmogorov-Smirnov 2 sampel. Hasil analisis bivariat dengan p<0,25 dianalisis lebih lanjut dengan uji multivariat regresi logistik untuk mengetahui variabel yang berpengaruh terhadap perubahan skor NIHSS.Hasil: Pada penelitian ini didapatkan 42 subjek dengan rerata usia 61,6±12,3 tahun dan jenis kelamin dominan laki-laki. Tidak didapatkan hubungan yang bermakna antara kadar NSE serum dengan ? NIHSS stroke iskemik akut (p=0,446).Diskusi: Kadar NSE serum tidak berhubungan dengan perubahan skor NIHSS stroke iskemik akut, terdapat hubungan bermakna antara status BMI dengan perubahan NIHSS.Kata kunci: NSE serum, ? NIHSS, stroke iskemik akut